DRUG ABUSE- A MEDICOLEGAL ASPECT - Mandal, Birendra Kumar; Yadav, Bishwa Nath (Journal of Drug Delivery and Therapeutics, 2012)
Drug abuse is an improper use of a therapeutic or non therapeutic drug resulting impulses to use that leads to significant problems or distress. Drug dependence is used to cover both drugs of addiction i.e. which cause both psychological and physiological dependence, as well as drugs which only cause habit formation i.e., which cause only psychological dependence. A part from medical problems drug abuse is a constant threat to family, society, nation and the world. This paper will aim to explore its different definitions and related issues.Keywords: Drug abuse, Dependence, Addiction.